Peranan Fasilitator Pendamping Untuk Meningkatkan Pendapatan Dan Skill Nasabah Btpn Syariah Kec. Wiyung Dalam Berwirausaha - Andramaya Kusuma Ningtyas; Siti Ning Farida (International Forum of Researchers and Lecturers, 2024)
The economy in Indonesia is starting to experience an increase in income. It can be seen today that many people choose to become entrepreneurs. PT Bank BTPN Syariah Tbk carries out the